Using the Rheological Index to Quantitatively Evaluate the Mechanical Performance of High-Elasticity Modified Asphalt - Jiani Wang; Zhongjun Xue; Meng Guo; Shuaixiang Zhang (Advances in Materials Science and Engineering)
High-elasticity modified asphalt is widely used in OGFC and bridge deck paving due to its high viscosity and strong displacement recovery capacity. It can improve the high-temperature deformation resistance and elastic recovery ability of the pavement. Especially in bridge deck pavement, high-elastic modified asphalt can inhibit the formation of reflective cracks and extend the service life. In order to quantitatively evaluate properties of the high-elasticity modified asphalt, rheological properties are studied by using a dynamic shear rheometer (DSR) test. The parameters were fitted with the Burgers model, and the constitutive equation was established. The 3 s elastic recovery rate Er was proposed to quantitatively evaluate the elastic recovery of high-elasticity modified asphalt. The experimental results show that the instantaneous modulus of elasticity G0 and the delayed modulus of elasticity G1 can be used to evaluate the elastic capacity. Er can quantitatively evaluate the elastic resilience of high-elasticity modified asphalt. The correlation coefficient between the test results of high-elasticity modified asphalt and those of impact toughness evaluation reached 0.9966, and the 3 s elastic recovery rate Er could be used to evaluate the elastic recovery ability of high-elasticity modified asphalt.